GOVERNMENT POLICIES IN MANAGING UNEMPLOYMENT AS A FORM OF COMMUNITY ECONOMIC RECOVERY POST COVID-19 - Syahfitri, Triyana (KARYA ABDI, 2023)
The focus of this study is to find a picture related to the government’s efforts to overcome the problem of unemployment. The method of writing this study uses library research. The results of the study show that: government efforts to overcome unemployment can be done through several forms, namely (1) the availability of accurate information related to employment; (2) the implementation of job training; (3) supervision related to improving the quality of education and entrepreneurship; (4) increasing socialization related to information literacy based on social inclusion. The suggestion that can be given by the writer is that the Government needs to be serious in overcoming the problem of unemployment by preparing policies, strategies and concrete steps to overcome the problem of unemployment. The government should collaborate with companies, educational institutions and / or training institutions in creating jobs so as to reduce unemployment in.